2021
DOI: 10.1186/s40545-021-00391-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of self-medication among university students in Ethiopia: a systematic review and meta-analysis

Abstract: Background Self-medication of medicines is a global issue particularly among those with good access and familiarity with medications such as university students. It has a significant impact on drug resistance and medication-related complications. There are limited and inconsistent studies on self-medication practices in Ethiopia. The aim of this systematic review and meta-analysis was to estimate the pooled prevalence of self-medication and its predictors among university students in Ethiopia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
8
0
3
Order By: Relevance
“…The highest prevalence of self-medication was related to students. A recent meta-analysis showed that the prevalence of self-medication in students (before the COVID-19 pandemic) was 49.5% ( 68 ). The prevalence of self-medication among college students seems to have increased during this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of self-medication was related to students. A recent meta-analysis showed that the prevalence of self-medication in students (before the COVID-19 pandemic) was 49.5% ( 68 ). The prevalence of self-medication among college students seems to have increased during this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The types, extent and motives may differ from one country to another, as well as the effects on society. 3,5 Mental disorders such as anxiety and depression are among the top ten leading causes of years lived with disability in the 10-49 age group worldwide. Health systems in most countries have not responded well to the situation due to the lack of equity between the need for treatment and its availability.…”
Section: Epidemiologymentioning
confidence: 99%
“…1,2,64 Time was another factor why young people did not go to a health professional, because in their opinion, not going to a health professional saves time. 3 The type of illness is another factor taken into account when carrying out actions regarding self-medication, since students classify their illnesses as serious and non-serious, so for nonserious illnesses they make use of their previous experience with medications, or consult with pharmacy personnel for the choice of drugs. 3 Among the student population, the academic year they are in also has an influence, as it is reported in a study conducted by Zeru 2020 in university students, that the prevalence of selfmedication in sixth year students is higher compared to first year students, due to their greater knowledge and understanding of drugs, which leads to greater confidence in self-diagnosis and its management.…”
Section: Factors Associated With Self-medicationmentioning
confidence: 99%
See 2 more Smart Citations